Is postoperative hyponatremia a real threat for total hip and knee arthroplasty surgery?. Issue 20 (15th May 2020) - Sinno, Ennio; De Meo, Daniele; Cavallo, Armando Ugo; Petriello, Luisa; Ferraro, Daniele; Fornara, Gianluca; Persiani, Pietro; Villani, Ciro
Abstract : Abstract: Postoperative hyponatremia (POH) is thought to be a fearsome complication of orthopedic surgery. Primary aim of this cohort study was to evaluate the incidence of POH and its clinical relevance in elective surgery, outlining differences between total knee arthroplasty (TKA) and total hip arthroplasty, looking for the presence of any risk factor commonly related to POH. Four hundred two patients that underwent total hip arthroplasty and total knee arthroplasty performed between 2016 and 2017 were retrospectively examined. Serum electrolytes, hemoglobin, hematocrit, glucose, and creatinine were evaluated preoperatively and at day 0-I-II from surgery. Age, sex, body mass index, comorbidities, drugs, surgery data, transfusions, postoperative symptoms, and length of stay (LOS) were determined. All surgeries were performed by the same equipe. Patients had the same perioperative management, excluded those that took thiazides, already at risk of POH. Patients were divided in 2 groups: group A, patients with normal postoperative natremia (294 patients) and group B, patients who developed POH (108, 26.9%); 66.7% of these developed POH within 24 hours postoperatively. In group B mean postoperative natremia was 133.38 (127.78–134.85) mmol/L. Two patients (1.8%) developed moderate hyponatremia, no severe hyponatremia was documented. Type of surgery, operation time, LOS, and presence of postoperative symptoms did not show statistically significant differences within groups. At multivariate logistic analysis chronic use of thiazides was the only variable associated to a decreased risk of developing POH (OR = 0.39; P  = .03). Hemoglobin postoperative values (OR = 1.22; P  = .03), the need of postoperative transfusion (OR = 2.50; P  = .02) and diabetes (OR = 2.70; P  = .01) were associated to an increased risk of POH. Although 26.9% of our patients exhibited POH, the onset of this disorder had no implication on postoperative symptoms and on LOS. Diabetes and transfusion are factors most often associated to POH.